Analisis Laporan Keuangan Pada Perusahaan Sektor Bahan Baku Periode Tahun 2019-2020 (Studi Kasus PT Indocement Tunggal Prakarsa Tbk) - Apriliya, Anisa Winda; Suartini, Sri (Jurnal Ilmiah Wahana Pendidikan, 2025)
Indonesia, a developing country, continues to distribute infrastructure development evenly to improve community access and productivity and eliminate disparities in each region in Indonesia. Cement as the main building material, results in an increase in demand for cement raw materials every year. The cement industry in Indonesia is experiencing oversupply or oversupply. Using descriptive research methods. utilizing the subject and object of examination of the annual financial statements of PT. Indocement Tunggal Prakarsa Tbk in 2019-2020. The data was obtained through the Indocement website, namely indocement.co.id, using a quantitative method approach as an analytical technique. The dependent variable is the performance of the company PT. Indocement Tunggal Prakarsa Tbk period 2019 – 2020. The independent variable to measure the performance of PT. Indocement Tunggal Prakarsa Tbk in 2019 – 2020. The financial performance of PT Indocement Tunggal Prakarsa Tbk from a liquidity ratio of 297%, a solvency ratio of 17%, shows the company is able to pay off short and long term debt. The activity ratio is 0.87 times and the profitability ratio is 11%.